Resistant Bacteria in Broiler Litter Used as Ruminant Feed: Effect of Biotic Treatment - Solomon Efriem; Chris Sabastian; Shlomo Blum; Marcelo Fleker; Sameer J. Mabjeesh; Malka Britzi (Antibiotics, 2023)
The use of antimicrobial drugs and coccidiostats in poultry farming is widespread, with a significant proportion of these drugs being excreted and released into the environment. The residues of such drugs in poultry litter (PL) can result in the development of antibiotic-resistant bacteria. The impact of different biotic treatments (aerobic, anaerobic, and stacking) on broiler litter (BL) before its use as animal feed has not been studied extensively, nor have the differences between antimicrobial-dependent and independent broiler farms been investigated. This study aimed to determine the resistant bacteria in BL used as ruminant feed before and after litter treatment. The results show that the most resistant bacteria before BL treatment were the Enterococcus species. This study also found that the quantity of amoxicillin-resistant Enterococcus detected in samples from antimicrobial-dependent farms was significantly higher than in those from antimicrobial-independent farms. Additionally, 14% of bacteria were multi-resistant to tetracycline, sulfafurazole, and erythromycin in antimicrobial-independent farm litters, significantly lower than those measured in antimicrobial-dependent broiler farm litter. This study highlights the importance of better understanding, regulating, managing, and using animal waste appropriately to reduce the number of antibiotic-resistant bacteria and minimize the use of antimicrobials that carry high risks for animals, humans, and the environment